2006
DOI: 10.1002/cncr.22190
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic value of methylation profile in pleural fluid and serum from cancer patients with pleural effusion

Abstract: BACKGROUND.The objective of this study was to investigate the diagnostic value of methylation profiles for discrimination between malignant and benign pleural effusions. A secondary objective was to examine the concordance of methylation in samples of serum and pleural fluid.METHODS.The authors used methylation‐specific polymerase chain reaction (MSP) analysis to examine the promoter methylation status of 4 genes in patients with pleural effusion: death‐associated protein kinase (DAPK), Ras association domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
(33 reference statements)
1
29
0
4
Order By: Relevance
“…The presence of tumor cells makes it a good source of tumor genomic DNA, whereas the little amount of soluble DNA in cell-free pleural fluid has been proved to be sufficient for most molecular analysis. Several studies have reported their determination of methylated DNA spectrum and somatic mutations of the genes of K-ras, Rho, P53 and FHIT in cell-free pleural fluid in patients with various neoplastic malignancies [8][9][10]. All above collectively demonstrate the importance of pleural effusion in genetic and epigenetic studies.…”
Section: Introductionmentioning
confidence: 94%
“…The presence of tumor cells makes it a good source of tumor genomic DNA, whereas the little amount of soluble DNA in cell-free pleural fluid has been proved to be sufficient for most molecular analysis. Several studies have reported their determination of methylated DNA spectrum and somatic mutations of the genes of K-ras, Rho, P53 and FHIT in cell-free pleural fluid in patients with various neoplastic malignancies [8][9][10]. All above collectively demonstrate the importance of pleural effusion in genetic and epigenetic studies.…”
Section: Introductionmentioning
confidence: 94%
“…Effusion specimens studied for DNA methylation have been frozen at -80°C prior to analysis in the majority of studies [84][85][86][87], although freezing at -20°C has also been used [88]. Studies of effusion specimens applying proteomics used fresh samples, as well as samples frozen at -20°C or -80°C [89][90][91][92][93].…”
Section: Other Ancillary Testingmentioning
confidence: 99%
“…21,25 Certain genes such as DAPK, RASSF1A, p15, p16/INK4a, RARβ, MGMT and APC, are known to be methylated in many cancers, and have been studied in patients with MPE. [13][14][15][16] In these studies, methylation analyses (combined or not with cytology) improved diagnosis of MPE [13][14][15][16] avoiding the need of other invasive diagnostic tests. However, the application of methylation as a prognostic tool is still poorly explored in patients with MPE.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The transcriptional inactivation caused by promoter hypermethylation affects genes involved in important cellular pathways, and has been suggested as a diagnostic tool for PE. [13][14][15][16] However, there is practically no evidence of its relation with prognosis in patients with MPE. 17 Therefore we aim to analyze the hypermethylation status of the promoter region of tumor suppressor genes p16/INK4a, MGMT (O6-methylguanine-DNA-methyltransferase), BRCA1 (breastcancer susceptibility gene 1) and RARβ (retinoic acid receptor β) in pleural fluid, and its association with survival and other common clinical parameters in patients with MPE.…”
Section: Prognostic Value Of Aberrant Hypermethylation In Pleural Effmentioning
confidence: 99%